PENGARUH USIA, MASA KERJA DAN JENIS KELAMIN TERHADAP PRODUKTIVITAS KINERJA KARYAWAN DI PERUSAHAAN MANUFAKTUR PT. SAMITEX BANTUL DIY - Aan Tri Laksana; Beta Asteria (MANAJEMEN DEWANTARA, 2026)
The purpose of this study is to examine how employee productivity at PT Samitex Sewon in Bantul, Special Region of Yogyakarta, is impacted by age, duration of service, and gender. Data were gathered via surveys and a study of the literature using a quantitative research technique with descriptive and verification approaches. The sample consisted of production employees selected to represent real conditions in a textile manufacturing environment. The findings reveal that length of service has a direct, positive, and significant effect on productivity, as indicated by a regression coefficient of 0.418. This suggests that employees with longer work experience possess a stronger understanding of production processes, resulting in better performance. Gender also shows a significant influence, with a coefficient of 0.212, indicating that male employees tend to demonstrate higher productivity in physically demanding tasks. In contrast, age does not significantly affect productivity due to the relatively homogeneous productive age range of the employees. Overall, the three variables collectively show a significant impact on productivity, as evidenced by an F-statistic value of 15.938 and a coefficient of determination of 0.527. These results highlight the importance of work experience and physical capacity differences in shaping productivity within the textile manufacturing sector. The findings also provide a basis for companies to develop more effective human resource strategies aimed at improving overall employee productivity